Dampak Media Sosial Terhadap Penggunaan Bahasa Gaul di Aplikasi Tiktok Pada Remaja - Romauli Situmorang; Rut Sahana Manalu; Kiki Renhardi Napitupulu; Lili Tansliova (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research is a descriptive research with a qualitative approach, which aims to describe the phenomenon of slang use on TikTok. Data was collected through a closed questionnaire asking respondents' opinions, views and comments on the use of slang. The results show that the use of slang on TikTok influences daily language use, with respondents using slang more than good and correct Indonesian. This research provides an in-depth insight into how slang develops on digital platforms and how it affects adolescents' communication and social identity. The findings are expected to inform further discussions on the balance between the adoption of slang and standardized and correct Indonesian.